Performance Analysis of Power Link Budget and Rise Time Budget to Support Fiber Optic Connectivity Telkom University - Iqbal, Muhammad (Jurusan Informatika, 2025)
Faculty of Applied Sciences, Telkom University has an Optical Communication System Laboratory designed as a supporting facility for the Optical Communication System course. One of the main obstacles is that this laboratory does not yet have a miniature Fiber to the X (FTTX) network like the optical cable-based internet network topology owned by internet service providers, resulting in a digital divide and limited practical experience for students. To overcome this problem, the development of an optical cable layout on a special FTTX network was applied to the Optical Communication System laboratory, so that participants understand the concept of Optical Distribution Cabinet (ODC) to Optical Distribution Point (ODP). The results of this study indicate that the fiber optic cable layout has succeeded in connecting the Optical Line Termination (OLT) at the Faculty of Applied Sciences to the Optical Distribution Point (ODP) 800 meters away (Hotel Lingian), as well as connecting to several laboratories in the Faculty of Applied Sciences environment that are connected to the Optical Distribution Center (ODC). The results of the Power Link Budget measurements for Downlink and Uplink and Bit Error Rate have values of -23.920 dBm, -24.631 dBm, respectively. While the Rise Time Budget value in uplink, downlink conditions with a value of 0.334 ns and 0.426 ns and the results of the Bit Error Rate (BER) are 16.37 × 10^(-13) and 15.25 × 10^(-12). The measurement value shows that the design has met the standards of the existing value parameters.